Chebulinic acid isolated from aqueous extracts of Terminalia chebula Retz inhibits Helicobacter pylori infection by potential binding to Cag A protein and regulating adhesion - Ou, Ling; Hao, Yajie; Liu, Hengrui; Zhu, Zhixiang; Li, Qingwei; Chen, Qingchang; Wei, Ruixia; Feng, Zhong; Zhang, Guimin; Yao, Meicun (Frontiers in Microbiology, 2024)
Background: Terminalia chebula Retz, known as the King of Tibet, is considered a functional food in China, celebrated for its antioxidant, immune-modulating, antibacterial, and anti-inflammatory properties. Chebulinic acid, derived from aqueous extracts of Terminalia chebula Retz, is known for its anti-inflammatory properties. However, its potential as an anti-Helicobacter pylori (HP) agent has not been fully explored.Methods: Herein, we extracted the main compound from Terminalia chebula Retz using a semi-preparative liquid chromatography (LC) system and identified compound 5 as chebulinic acid through Ultra-high performance liquid chromatography-MS/MS (UPLC-MS/MS) and Nuclear Magnetic Resonance (NMR). To evaluate its role, we conducted minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays, scanning electron microscope (SEM) imaging, inhibiting kinetics curves, urea fast test, cell counting kit-8 (CCK-8) assay, western blot analysis, griess reagent system, and molecular docking.Results: Our results showed that chebulinic acid effectively inhibited the growth of the HP strain ATCC 700392, damaged the HP structure, and exhibited selective antimicrobial activity without affecting normal epithelial cells GES-1. Importantly, it suppressed the expression of Cytotoxin-associated gene A (Cag A) protein, a crucial factor in HP infection. Molecular docking analysis predicted a strong affinity (-9.7 kcal/mol) between chebulinic acid and Cag A protein.Overall, our findings suggest that chebulinic acid acts as an antiadhesive agent, disrupting the adhesion of HP to host cells, which is a critical step in HP infection. It also suppresses the Cag A protein. These results highlight the potential of chebulinic acid against HP infections.